Utilisation of and Attitude towards Traditional and Complementary Medicine among Ebola Survivors in Sierra Leone - Peter Bai James; Jon Wardle; Amie Steel; Jon Adams (Medicina, 2019)
Background and objectives: In addition to conventional healthcare, Ebola survivors are known to seek traditional and complementary healthcare (T&CM) options to meet their healthcare needs. However, little is known about the general beliefs of Ebola survivors regarding T&CM and the impact of these beliefs in influencing their decisions around T&CM use. This study examines Ebola survivors’ attitudes towards T&CM use in Sierra Leone. Materials and Methods: We conducted a nationwide quantitative cross-sectional study of 358 Ebola survivors in Sierra Leone between January and August 2018. We used descriptive analysis, chi-square tests and backward stepwise binary logistic regression for data analysis. Results: Close to half of the survivors (n = 163, 45.5%) had used T&CM since their discharge from an Ebola treatment centre. Survivors who viewed T&CM as boosting their immune system/resistance were 3.89 times (95%CI: 1.57−9.63, p = 0.003) more likely to use T&CM than those who did not view T&CM as boosting their immune system/resistance. Additionally, survivors who viewed T&CM as having fewer side effects than conventional medicine were more likely to use T&CM [OR = 5.03 (95%CI: 1.92−13.19, p = 0.001)]. Ebola survivors were more influenced to use T&CM based on their personal experience of the effectiveness of T&CM than by clinical evidence [OR = 13.72 (95%CI: 6.10−30.84, P < 0.001)]. Ebola survivors who perceived T&CM as providing them with more control than conventional medicine over their health/body were more likely to use T&CM [OR = 4.15 (95%CI: 1.74−9.89, p = 0.001)] as opposed to those who did not perceive T&CM in this way. Conclusions: Considering the widespread use of T&CM, an understanding of Ebola survivors’ attitudes/beliefs towards T&CM is useful to healthcare providers and policymakers with regard to public education and practitioner−survivors communication, T&CM regulation and research in Sierra Leone. Ebola survivors appear to turn to T&CM not only for treatment, but also to fill gaps in conventional health care services.